Effect Of Lipid Levels On The Reproductive Performance Of Snakehead Murrel, Channa Striatus - Roshada Hashim; Alireza Ghaedi; Muhammad Anamul Kabir (Wiley, 2024)
Aquaculture ResearchVolume 47, Issue 3 p. 983-991 [TIADA PERMISSION AKSES FULLTEXT]